Degradation Behavior and Accelerated Weathering of Composite Boards Produced from Waste Tetra Pak® Packaging Materials - Yilgor, Nural; Kose, Coskun; Terzi, Evren; Figen, Aysel Kanturk; Ibach, Rebecca; Kartal, S. Nami; Piskin, Sabriye (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2014)
Manufacturing panels from Tetra Pak (R) (TP) packaging material might be an alternative to conventional wood-based panels. This study evaluated some chemical and physical properties as well as biological, weathering, and fire performance of panels with and without zinc borate (ZnB) by using shredded TP packaging cartons. Such packaging material, a worldwide well-known multilayer beverage packaging system, is composed of cellulose, low-density polyethylene (LDPE), and aluminum (Al). Panels produced from waste TP packaging material were also examined by FT-IR to understand the fungal deterioration and extent of degradation after accelerated weathering. Before FT-IR investigations, panel specimens were ground under nitrogen atmosphere due to non-uniformity of the composite material. The FT-IR results showed that fungal degradation occurred in the natural polymer of the panel matrix. Although the natural polymer is mostly composed of cellulose, there were also small amounts of polyoses and lignin. It was seen that especially polyose and lignin bands in FT-IR spectra were affected more than cellulose bands by fungal attack. No changes were observed by the fungi in the plastic component (LDPE) of the matrix; however, LDPE seemed more sensitive to weathering than cellulose. Incorporation of ZnB at loading level of 1% (w/w) did not contribute fire performance of the panels when compared to control panel specimens, while a loading level of 10% improved fire performance considering test parameters such as mass loss, ignition time and peak heat release rate.
Keywords: Tetra Pak (R) packages; Decay resistance; Weathering; Fire resistance; FT-IR; Zinc borate; Moisture sorption; Grinding with nitrogen; LOW-DENSITY POLYETHYLENE; WATER-ABSORPTION; POLYPROPYLENE COMPOSITES; MECHANICAL-PROPERTIES; CARDBOARD PANELS; BEVERAGE CARTON; WOOD; FTIR; ALUMINUM; SORPTION; Materials Science